Chapter 9 Which Patient Takes Centre Stage? Placing Patient Voices in Animal Research - Davies, Gail (Springer Nature, 2020)
The growth of personalised medicine and patient partnerships in biomedical research are reshaping both the emotional and material intersections between human patients and animal research. Through tracing the creative work of patients, publics, scientists, clinicians, artists, film-makers, and campaigning groups this chapter explores how 'patient voices' are being rearticulated and represented around animal research. The figure of 'the patient' has been a powerful actor in arguments around animal research, mostly 'spoken for' by formal organisations, especially in publicity material making ethical justifications for the need and funding of medical research. Here, patient voices make corporeal needs legible, gather expectations and resources, and provide the horizon for embodying future hopes. However, the accessibility of digital media, alongside local institutional experiments in openness, is creating alternative spaces for voicing patient interfaces with animal research. On research establishment websites, and elsewhere, patients' perspectives are emerging in short films, taking up positions as narrators, tour guides, and commentators, inviting the public to follow them into these previously inaccessible spaces. The embodied experience of patients, sometimes severely affected by the current absences in biomedical research, are used to authorise their presence in these places, and allow them to ask questions of animal researchers. The films are powerful and emotional vehicles for voicing patient experiences and opening up animal research. They also refigure the affective responsibilities around animal research, resituating a public debate around ethics within the body of the patient. The future expectations personified in the abstract figure of the patient, are rendered turbulent in the ambiguous corporeal encounter between human and animals undergoing similar experiences of suffering.